An oral cancer biobank initiative: a platform for multidisciplinary research in a developing country - Zain, R.B.; Athirajan, V.; Ghani, W.M.N.; Razak, I.A.; Latifah, R.J.R.; Ismail, S.M.; Sallam, A.A.; Bustam, A.Z.; Rahman, Z.A.A.; Hussien, A.; Talib, N.; Cheong, S.C.; et al. (Kluwer (now part of Springer), 2013)
Identification of diagnostic markers for early detection and development of novel and therapeutic agents for effective patient management are the main motivation for cancer research. Biological specimens from large cohort and case-control studies which are crucial in providing successful research outcomes are often the limiting factor that hinders research efforts, especially in developing countries. Therefore, the Malaysian Oral Cancer Database and Tissue Bank System (MOCDTBS) were established to systematically collect large number of samples with comprehensive sociodemographic, clinicopathological, management strategies, quality of life and associated patient follow-up data to facilitate oral cancer research in Malaysia. The MOCDTBS also promotes sharing among researchers and the development of a multidisciplinary research team. The following article aims to describe the process of setting-up and managing the MOCDTBS.